Biotechnology as strategies for reversal of contaminated areas by solid waste - Silva, Jaqueline de Santana da; Santos, Shalene da Silva; Gomes, Felippe George Gatti (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
With the uncontrolled cities population growth, the consumption of many products has become a serious problem as the disposal of unused parts (waste) ends up being deposited in places where, their remain for an extended period without treatment, promote a contamination of the area and can cause serious problems to human health and the environment. Contaminated areas are being recovered through biotechnology with environmental parameters modification. This induces and accelerates the removal of contaminants in water and soil, and reduce the time required for recovery of the contaminated area. Thus, this work was conducted through an analysis of available material in international databases SCIELO, LILACS, HIGHWIRE, PUBMED and SCIRUS, and includes several works that have been developed in the area of environmental remediation of pollutants, it aims to bring a brief clarification on two techniques that can be used for the recovery area with the presence of solid waste (RS), the bioremediation and the phytoremediation involving the use of microorganisms and plants for the recovery of these contaminated areas.